EMPLOYEE TURNOVER IN HYBRID ORGANIZATIONS: THE ROLE OF PUBLIC SECTOR SOCIALIZATION AND ORGANIZATIONAL PRIVATENESS. (12th October 2015) - KRØTEL, SARAH M.L.; VILLADSEN, ANDERS R.
Abstract : Public sector reforms are increasingly blurring the boundaries between the public and private sectors, making way for hybrid organizations existing between the two sectors. While research has begun to explore organizational hybridity and how it affects employee identities and outcomes, knowledge about employee behaviour in hybrid organizations is scarce. Public–private hybrid organizations face the challenge of balancing some degree of privateness with traditional public sector practices and values. In this article we focus on public sector companies as an increasingly prevalent type of hybrid organization, and how employee turnover is affected by the degree of organizational privateness. We suggest that highly socialized public sector employees are more likely to leave when their organization exhibits higher levels of privateness. In an empirical study of all employees in public sector companies in Denmark we find support for this theory. The article contributes new knowledge about employee turnover dynamics and how the balance of opposing demands in hybrid organizations has implications for employee behaviour.